La socio-afectividad en la calidad del rendimiento académico de los estudiantes de tercer año de educación básica de la unidad educativa “francisco huerta Rendón” de la ciudad de Babahoyo de la Provincia de los Ríos - Ruiz Velásquez, Josellin Andreina (2016)
The presente work describes the degree of participation of teachers, parents of family and children of the Educational Unit Francisco Huerta Rendón of canton Babahoyo in the esducational activities of their children. The participation of parents in the education of their children is very important. When parents participate in teaching their children , children usually perform better at the school, behave better, and have more attitudes toward school and grow to be more successful in life. The results show that the participating of teachers and parents in the school of children depends in the school of three main factors. 1 Communication with the school 2 Communication with the child 3 School knowledge. In general, the participation of parents in the esducational activities of children is a great affective motivation as children are motivated by their parents and improve their academic preformance this was classified as low or precarious. Especially in relation to the factors of communication and knowledge of school, while the mothers had a significantly higher level of participation in both factors.The implications of results for school research on socio affective development in children in the educationalprocess are discussed in light of the results.